Beta-hydroxy-beta-methyl butyrate supplementation in critically ill patients: a systematic review and meta-analysis of randomized controlled trials - Ren, Yu; Gao, Ya-Bei; Yu, Da-Xing; Huang, Hui-Bin (Frontiers in Nutrition, 2025)
BackgroundBeta-hydroxy-beta-methylbutyrate (HMB) is beneficial for restoring muscle mass. However, the evidence supporting its use in critically ill patients remains unclear. We conducted a systematic review and meta-analysis of HMB in this population to ascertain its effects.MethodsWe searched PubMed, Embase, China National Knowledge Infrastructure, Wanfang, and the Cochrane database for articles focusing on adult patients receiving HMB compared to controls. The primary outcome was mortality. To explore potential heterogeneity, we assessed study quality and performed subgroup analysis, sensitivity analysis, and quality of evidence.ResultsNine randomized controlled trials were included. There were some differences in the study design, HMB protocols, and muscle measurements among these trials. Overall, there were no significant differences in mortality between the HMB and the control groups (risk ratio = 0.96; 95% CI, 0.44–2.08; P = 0.92). This finding was confirmed by the subgroup and sensitivity analyzes. Patients in the HMB group had similar durations of MV [mean difference (MD), –0.40; 95% CI, –0.91 to 0.12; P = 0.13], ICU stay (MD, –0.61 days; 95% CI, –3.59 to 2.38; P = 0.69), and hospital stay (MD, 1.52 days; 95% CI, –1.18 to 4.22; P = 0.27). In addition, HMB did not affect changes in body weight (P = 0.53), body mass index (P = 0.56), or quadriceps thickness (P = 0.74). The outcomes of changes in skeletal muscle area (P = 0.95) and muscle loss (P = 0.16) were similar between the two groups.ConclusionBeta-hydroxy-beta-methylbutyrate (HMB) did not improve the mortality or other clinical outcomes in critically ill patients. This may be because of the different HMB strategies used in the included trials. Our findings provide insights into future research designs that explore the clinical efficacy of HMB in this patient population.